The secrets of character : writing a hero anyone will love - Bird, Matt (Screenwriter) (Writer's Digest Books, 2022)
"The hardest yet most essential element of writing great fiction is character - specifically, creating a central hero who is relatable, compelling, and worth the reader's precious time. In this entertaining and practical guide, popular blogger, writing coach and screenwriter Matt Bird breaks down what makes characters embraceable and unforgettable, and presents insider tips and tricks for writers of all levels and genres. Generously packed with examples from popular books and movies analyzed with engaging specificity, this expert guide reveals what makes audiences believe, care, and invest in great characters - and how to bring your own characters vividly to life"--